A Day in the News A Stylistic Analysis of Newsspeak - Morini, Massimiliano (Linguistic Insights, 2018)
A Day in the News is the linguistic description of a single day in the life of the British press - Wednesday, 19 August 2015. Employing a variety of tools and methods - from multimodality to pragmatics, from close reading to computational stylistics - Morini looks at nine different «journalistic worlds» and their respective «Newsspeaks». The results are often revealing: by providing its readers with an accurate idea of the universe projected by each paper, this study revises many received ideas on the clear-cut boundaries separating «popular» from «highbrow» journalism. In the process, A Day in the News also sums up more than three decades of work on the language of newspapers, and provides a general analytical method for journalism in the digital age. The three chapters of the book focus, respectively, on the multimodal features of newspapers and their e-editions; on the quantitative prominence accorded to certain wordings and topics in each newspaper; and on the ideological/evaluative slant with which news items are presented and commented. Throughout, the focus is not on some outmoded notion of journalistic style, but on the degrees of proximity or distance presupposed by different formats, layouts and linguistic registers.